EDUCATIONAL CONTENT, INFORMATION QUALITY, AND BRAND AWARENESS: A STUDY OF INSTAGRAM USERS IN TANGERANG - Alya Fitria Sari; Yanti Susanti; Zahra Allya Dika; Eisya Sabilatul F. (PT. ZILLZELL MEDIA PRIMA, 2026)
The development of digital technology has changed the pattern of communication in society, with Instagram now becoming the main platform for brands to build awareness through visual and informative content. This study aims to examine the influence of educational content and information quality on the level of brand awareness among Instagram users in Tangerang City. Using a quantitative approach with an explanatory survey method, this study involved a population of 300 Instagram users. The research sample consisted of 75 respondents determined using the Slovin formula with non-probability sampling techniques. Data were collected through a Likert scale questionnaire and analyzed using multiple linear regression. The results show that, partially, educational content has a positive and significant effect on brand awareness (t-count 3.223 > t-table 2.645). Similarly, information quality has a positive and significant effect (t-count 4.914 > t-table 2.645) and is the most dominant variable. Simultaneously, both variables had a significant effect with an F-value of 96.048 and contributed 72.7% to the variation in brand awareness. This study concluded that the combination of educational content and accurate information presentation is very effective in strengthening brand memory among social media users.